Pengukuran Keterampilan Komunikasi Siswa Setelah Pandemi Covid 19 [Measuring Students' Communication Skills After the Covid-19 Pandemic] - Krisdianto, Patricius Dwi; Widjaya, Wahyu; Christianingsih, Ni Putu Hindriani; Rizki Raindriati (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2024)
Communication skills are essential for everyone, including students. The COVID-19 pandemic had a significant impact on the education sector, with learning heavily relying on students' ability to use information technology. During this period, communication and interaction depended on the quality of the hardware used and the stability of internet connections. Due to unprecedented restrictions, these limitations affected students' communication skills, both written and verbal. There have been assumptions and speculations from teachers and parents that students' communication skills have declined after the pandemic. This study aims to understand how well students have developed their communication skills post-pandemic. Research employs a quantitative research method. Data was collected by distributing open-ended questionnaires to 6th-grade students at XYZ Elementary School. A total of 45 students participated in the study. The results of this study indicate that the average communication skills of the students at XYZ Elementary School in Tangerang after the pandemic are considered adequate. Therefore, teachers need to focus on improving students' communication skills to enhance them further.